High-Frequency Trading around Macroeconomic News Announcements: Evidence from the U.S. Treasury Market - George J. Jiang; Ingrid Lo; Giorgio Valente (Bank of Canada, 2014)
This paper investigates high-frequency (HF) market and limit orders in the U.S. Treasury market around major macroeconomic news announcements. BrokerTec introduced i-Cross at the end of 2007 and we use this exogenous event as an instrument to analyze the impact of HF activities on liquidity and price efficiency. Our results show that HF activities have a negative effect on liquidity around economic announcements: they widen spreads during the pre-announcement period and lower depth on the order book during the post-announcement period. The negative impact on liquidity mainly derives from HF trades. Nonetheless, HF trades improve price efficiency during both the preannouncement and post-announcement periods.
Keywords: G10; G12; G14; 330; Financial markets